The correlates of workplace bullying on employees’ health and well-being among frontline employees - Daniella Mokhtar,; Haikal Anuar Adnan,; Najwa Afiqa Roshaizad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Workplace bullying has been a growing interest among researchers from various disciplines including psychology and management studies. This study examines the relationship of bullying and the consequences on employees’ health and well-being within the workplace context. A sample of 284 employees from various organizations in the Klang Valley area participated in this three-wave study with a final number of 70 employees which responded at all three time points. The survey covers a number of variables including experiences of being mistreated (Negative Acts Questionnaire), mental health (DASS), psychosomatic complaints (Physical Health Questionnaire) as health and well-being outcomes. Results showed an average of 80% of the participants were at least exposed to negative behaviors at the workplace and an average of 15% were victims of workplace bullying experiencing negative acts at least on a weekly basis if not daily.